2018
DOI: 10.3389/fnhum.2018.00316
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Hangover Increases Conflict Load via Faster Processing of Subliminal Information

Abstract: The detrimental effects of acute alcohol intoxication and long-term alcohol (ab)use on cognition are well-known. Yet, only little is known about the cognitive effects of an acute alcohol hangover, even though it might affect executive functions associated with workplace performance or driving skills. Given that alcohol hangover may increase the speed of information accumulation, we assessed the behavioral effects of conflict load (induced by a subliminal prime) on cognitive control, as assessed via the Flanker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…This way, a distractor, especially if previously encountered, may prime certain responses -even when they are no longer needed or correct. While previous studies have suggested that acute alcohol intoxication does not seem to strongly impair S-R binding [22], this has never been investigated in the hungover state, which may functionally differ from the intoxicated state [17,18]. Of note, there are several mechanisms which could drive such differences, including differential modulation of gamma-aminobutyric acid (GABAergic) signaling by ethanol and its metabolite acetaldehyde, which is likely responsible for feeling hungover [23][24][25], and immunological parameters, including those related to inflammation While previous studies have suggested that acute alcohol intoxication does not seem to strongly impair S-R binding [22], this has never been investigated in the hungover state, which may functionally differ from the intoxicated state [17,18].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…This way, a distractor, especially if previously encountered, may prime certain responses -even when they are no longer needed or correct. While previous studies have suggested that acute alcohol intoxication does not seem to strongly impair S-R binding [22], this has never been investigated in the hungover state, which may functionally differ from the intoxicated state [17,18]. Of note, there are several mechanisms which could drive such differences, including differential modulation of gamma-aminobutyric acid (GABAergic) signaling by ethanol and its metabolite acetaldehyde, which is likely responsible for feeling hungover [23][24][25], and immunological parameters, including those related to inflammation While previous studies have suggested that acute alcohol intoxication does not seem to strongly impair S-R binding [22], this has never been investigated in the hungover state, which may functionally differ from the intoxicated state [17,18].…”
Section: Introductionmentioning
confidence: 95%
“…While previous studies have suggested that acute alcohol intoxication does not seem to strongly impair S-R binding [22], this has never been investigated in the hungover state, which may functionally differ from the intoxicated state [17,18]. Of note, there are several mechanisms which could drive such differences, including differential modulation of gamma-aminobutyric acid (GABAergic) signaling by ethanol and its metabolite acetaldehyde, which is likely responsible for feeling hungover [23][24][25], and immunological parameters, including those related to inflammation While previous studies have suggested that acute alcohol intoxication does not seem to strongly impair S-R binding [22], this has never been investigated in the hungover state, which may functionally differ from the intoxicated state [17,18]. Of note, there are several mechanisms which could drive such differences, including differential modulation of gamma-aminobutyric acid (GABAergic) signaling by ethanol and its metabolite acetaldehyde, which is likely responsible for feeling hungover [23][24][25], and immunological parameters, including those related to inflammation [26,27].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations